Magic(al) realism - Bowers, Maggie Ann (Routledge, 2004)
This volume explores the many definitions and terms used in relation to the genre of 'magic' or 'magical' writing. It traces the origins of the movement in painting and fiction and offers an historical overview of the contexts for magic(al) realism.
Keywords: Geschichte 1900-2000; Letterkunde; Magisch realisme; Réalisme magique (Art); Literatur; Arts, Modern -- 20th century; Magic realism (Art); Magischer Realismus -- Literatur; Magischer Realismus -- Kunst